How important is extra solids-not-fat in your milk? - H.A. Roberts (Kansas Agricultural Experiment Station Research Reports, 1987)
Milk with high solids-not-fat is valuable to the consumer for its flavor and nutritional value and to the manufacturer of milk products, especially relating to cheese yield. Solids-not-fat consists of all solids in milk other than fat. Protein is the most important component of milk because of its nutritional value and its functional properties. Other components, such as milk fat and lactose, also contribute to milk quality and impart certain characteristics to milk products but to a lesser degree.; Dairy Day, 1987, Kansas State University, Manhattan, KS, 1987;
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-114-S; Report of progress (Kansas Agricultural Experiment Station); 527; Dairy; Milk; Nutritional value; Protein; Lactose; Ash (Minerals); Milk Fat